A Critical Assessment of the South African Intelligence Agency - Loubser, F. G. (Koers, 2025)
This article analyses the state of the intelligence community (IC) in the South African context to determine whether the IC is a failure or whether it is a total disaster. Due to a failed, insufficient intelligence system, the current world order has been severely disrupted by two wars. In this regard, the focus is in particular on the situation in the Middle East, where Israel and the Palestinian group HAMAS are currently involved in a war. According to a Reuters report (Nakhoul & Saul, 2023), Israel was caught off guard by the HAMAS attack on 7 October 2023, and several people have died since then. These types of violent incidents recall the violent riots/protests in South Africa in July 2021, where the severe action of the people involved overpowered the South African Police Service (SAPS) and South African intelligence services. These protest actions / riots inflicted millions of rand in infrastructure damage, and hundreds of people died. The Expert Panel, appointed by the President of South Africa in July 2021, commented as follows on this protest action: "The question, many argue, is not if and whether more unrest and violence will occur, but when it will occur." (Presidency, 2021) A conceptualised intelligence risk management framework (IRMF) is used to analyse the IC of South Africa, with a specific focus on the State Security Agency (SSA). The article aims to explore, describe, and analyse the status and activities from a democratically based framework. Furthermore, the article aims to evaluate the failures of the past decades and draw conclusion regarding the current status of intelligence agencies or services in South Africa. This analysis will determine whether the IC is ready and capable of addressing these types of threats and risks in the future.